Code-Mixing and Code-Switching in Maths Online Classroom: The Language Function in Interaction of Junior High School Students - Cici Melysa; Erika Sinambela; Arsen Nahum Pasaribu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The research was conducted as a qualitative case study. The study's aims were to look into the types for codes and the reasons in the occurrence of code-mixing and code-switching. In this study, a teacher and 20 students of Junior High School students were the subjects. The information was gathered through observation, recording and interview. As the result of this research, the language function in code-mixing and code-switching found for interpersonal function in 42 cases in 56,75%. The least function of language found during the online interaction was personal function with 5 cases in 6,76%. Directive function found during the online interaction in Junior High School teacher-students in NGS is 17,57%. Meanwhile, referential function was highly used more than directive function in almost 19% detected. From the data, it was concluded that the speaker in the classroom tended to interact by using interjection in Bahasa Indonesia even though in the interaction of English Language. Based on the analysis, the types of code-mixing are elaborated into three categories, as follow: insertion (50%), alternation (28,57%) and congruent lexicalization (21,43%). On the other hand, there are three types of code-switching: tag switching (88,52%), inter sentential switching (9,84%) and intra sentential switching (1,67%). The reasons of using code-mixing and code-switching based on previous findings are talking about particular topic (21,43%), being emphatic (7,14%), intention for clarifying (35,71%) and lexical needed (35,71%). Meanwhile, based on the interview, the reasons of using code-mixing and code-switching is due to the environmental society impact which cause the language usage of the speakers.